PERAN BADAN USAHA MILIK DESA (BUMDES) DALAM MENINGKATKAN KESEJAHTEAAN MASYARAKAT DESA TELUK PAPAL KECAMATAN BANTAN KABUPATEN BENGKALIS - Hartono Rudi; Garnasih Lestari Raden; Novrianti Puspita Dian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the role of village-owned enterprises (BUMDes) inimproving the welfare of the people of Teluk Papal Village, Bantan District,Bengkalis Regency. The population in this study included all the people of TelukPapal Village, Bantan District, totaling 655 people. Primary data was collectedusing a questionnaire as an instrument to prove the results of the study. To test thehypothesis in this study, the Likert scale interval was used with the help of theSPSS program. The sampling technique that has been chosen is non-probabilitysampling (64 users of savings and loan services at BUMDes Teluk Papal Village,Bantan District, Bengkalis Regency). The results of the study show that VillageOwned Enterprises (BUMDes) do not yet have a role in improving the welfare ofthe people of Teluk Papal Village, Bantan District, Bengkalis Regency, RiauProvince. Keywords: Role, Village Owned Enterprises (BUMDes), Community Welfare